How do energy input and carbon emission constraints affect the ESG performance of manufacturing enterprises? Evidence from China - Sen Wang; Jinye Li (Sustainable Futures)
Sustainable development is the key to achieving high-quality growth in the manufacturing industry. The article analyzes the impact of energy inputs and carbon emission constraints on the ESG performance of Chinese manufacturing firms using listed company data from 2011-2022, carbon market emission control firms, and new energy city policies. The study finds the following core conclusions. First, energy input-carbon emission constraints can significantly improve the overall ESG performance of manufacturing firms rather than being limited to improving one aspect of performance. The benchmark regression results remain robust after a series of robustness tests. Second, the mechanism test shows that the energy input-carbon emission constraint can improve the ESG performance of manufacturing firms by promoting public green concern in the source prevention link, corporate green technology innovation in the process control link, and corporate green investment in the end governance link. In addition, enterprises' horizontal competition and vertical cooperation factors have a moderating effect on the direct impact of energy input-carbon emission constraints. Supply chain integration as a vertical cooperation factor positively reinforces the marginal increment. Firm competitiveness as a horizontal competition factor produces a ''U'' shaped moderating effect that is first weak and then strong. Finally, the heterogeneity analysis finds that the energy input-carbon emission constraint effectively promotes the ESG performance of technology-intensive and mature manufacturing firms and has a ''sending charcoal in the snow'' effect on the ESG performance of manufacturing firms in high-carbon industries. Therefore, the two-end synergistic constraint of energy input-carbon emission can effectively promote the growth of ESG performance of manufacturing enterprises, which brings important insights to the green development of manufacturing industries in other countries.